RHETORICAL TECHNIQUES ON REDDIT’S RACIST JOKES - LUTFI S, RIZKY (LANGUAGE HORIZON, 2017)
Abstract This study will be focus on analyzing the racist jokes in Reddit’s dark humor forum, from rhetorical perspective. This research uses theory of rhetorical technique by Berger (1995) to identify the techniques used by the creator of humor. The data was taken from Reddit, and the research employed descriptive qualitative method, embracing the characteristics of a qualitative texts analysis. The results of this research shows that among the four categories of rhetorical techniques proposed by Berger, there are only three categories that were found in the data, those are; Language-based, Logic-based, and Identity-based. The last category which is Visual-based technique, was not found in the data, since the data was in a form of texts, instead of picture or video. Keywords: Racist Joke, Rhetorical Techniques .   Abstrak Studi ini akan fokus menganalisa lelucon rasis yang ada di forum dark humor Reddit, melalui perpektif retorika. Penelitian ini menggunakan teory teknik retorika oleh Berger (1995) untuk mengidentifikasi eknik-teknik yang digunakan oleh pencipta humor. Data-data diambil dari Reddit, dan penelitian ini mengaplikasikan metode penelitian deskriptif kualitatif, yang memegang karakteristik dari analisa teks kualitatif. Hasil dari penelitian ini menunjukan diantara empat kategori dari teknik retorika yang di kemukakan Berger, hanya ada tiga kategori yang diketemukan pada data, di antaranya; Languange-based, Logic-based, dan Identity-based. Kategori terakhir yaitu tenik Visual-based, tidak di ketemukan karena data yang di ambil berbetuk tulisan, bukanlah gambar atau video. Kata Kunci: Lelucon Rasis, Teknik Retorika.